Characterization of Ultrafine Silica Prepared from Rice Husk Ash by Sol-Gel Method. Issue 1 (February 2021) - Qurrota A'yuni, Dewi; Djaeni, Mohamad; Subagio, Agus
Abstract: Rice husk ash that is removed from the combustion process in a furnace has a potential for silica source through the sol-gel process. The experiment was conducted in different concentrations of sodium hydroxide solution of 5.0, 7.5, and 10.0 % w/v in the preparation of the sodium silicate solution. For further observation, different pH values of the gel solution were also examined with values of 1 to 7. Particle Size Analyzer (PSA) has been used for size characterization of samples, while Energy Dispersive X-Ray Spectrophotometer (EDS) was used to determine the composition of the powder. The result shows that for all cases the silica products still contain carbon materials. The different pH values of the silica gel solution exhibit a different physical appearance of the gel. At pH values of 5 to neutral 7, the silica gel is completely formed, while in more acidic conditions there are only precipitates or none of both. Mostly, silica particles were in the size of micrometers with more than 90% in the range of 2-128 µm. The composition characterization showed different percentages of silica and the good result was found at 5.0% of sodium hydroxide solution with a gel solution pH of 7.